Mixed motives: an empirical analysis of ILO roll-call votes - Bernhard Boockmann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
In this empirical paper, we look at individual voting behaviour of government delegates to the International Labour Organization (ILO). We distinguish between the instrumental motive for voting, which consists in the chance that ones vote may turn the balance in favour of ones preferred outcome, and non-instrumental motives, such as a desire for good reputation. Empirically, the two can be identified because two alternatives, abstaining and not participating in the vote, do not differ in their instrumental value, but are likely to differ with respect to reputation aspects. The model is estimated by a multinomial logit with country-specific unobserved heteroge-neity, using roll-call votes on the final passage of ILO conventions from 1977 to 1995. The hypothesis that voting is only instrumental is clearly rejected by the data.
Keywords: D78; 330; Voting; discrete choice; international labour standards; ILO; Internationale Sozialstandards; Abstimmung; Präferenztheorie; Schätzung; Welt; International Labour Organisation